A national UK audit for diagnostic accuracy of preoperative CT chest in emergency and elective surgery during COVID-19 pandemic. Issue 9 (September 2020) - Callaway, M.; Harden, S.; Ramsden, W.; Beavon, M.; Drinkwater, K.; Vanburen, T.; Rubin, C.; Beale, A.
Abstract : AIM: To report on a snap audit of all departments in the UK as to the value of preoperative thoracic imaging, preferably computed tomography (CT), of patients undergoing any surgery to assess for changes consistent with COVID-19 preoperatively. MATERIALS AND METHODS: All Imaging departments in the UK were contacted and asked to record the number of preoperative CT examinations performed in patients being considered for both emergency and elective surgical intervention over a 5-day period in May 2020. RESULTS: Forty-seven percent of departments replied with data provided on >820 patients. Nineteen percent of additional preoperative CT was in patients undergoing elective intervention and 81% in patients presenting with surgical abdominal pain. There was a high rate of false positives in patients who tested negative for COVID-19, producing a sensitivity for thoracic CT of 68.4%. CONCLUSION: This UK-wide audit demonstrates that a large number of additional thoracic imaging examinations over a 5-day period were performed with a low sensitivity for the identification of COVID-19 in this preoperative group of patients. Given these findings, it is difficult to justify this additional examination in this group of patients. Highlights: Pre operative CT has little role in the management of patients undergoing emergency surgery during the COVID-19 pandemic. Pre operative CT has little role in the management of patients undergoing elective surgery during the COVID-19 pandemic. Preoperative CT represents a considerable additional imaging workload.